Error Analysis and Its Implications for the English Classroom: A Case Study of an Advanced English Learner - Millatul Islamiyah; Muchamad Sholakhuddin Al Fajri (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2019)
This study aims to examine English spoken language uttered by Indonesian EFL learners by employing error and interlanguage analysis. It principally focuses on highlighting the value of error and interlanguage analysis on the development of Indonesian English language teaching classroom. The data were in the form of language transcription taken from a structured sociolinguistics interview with an advanced English learner. The results indicate that errors, either on phonological, grammatical, lexical, or pragmatic competence, are principally caused by L1 or interlingual transfer, despite few occurrences of developmental errors. Regarding the implication of this study for language classroom, it offers several suggestions for improving English language classroom including an introduction of varieties of chunk languages and adjacency pairs used across cultures to students.